A comprehensive review of cereal germ and its lipids: Chemical composition, multi-objective process and functional application. (15th November 2021) - Wang, Jingyi; Tang, Junyu; Ruan, Shaolong; Lv, Ruiling; Zhou, Jianwei; Tian, Jinhu; Cheng, Huan; Xu, Enbo; Liu, Donghong
Graphical abstract: Highlights: New functions of CG lipids depending on their dosages are discussed. Thermal/non-thermal processes slightly change fatty acid composition of CG lipids. Composite treatments enhance both the stability and nutrition of CG and CG lipids. CG matrices/lipids are applied as animal fat replacement and nutrition supplement. Abstract: Cereal germ (CG), a by-product of grain milling, has drawn much attention in the food industry because of its nutritional and functional advantages. Nowadays, the utilization of cereal germ from animal feeds to foodstuff is a popular trend. CGs have high content of polyunsaturated fatty acids in their lipids (43.9–64.9% of total fatty acids), but they are also induced to oxidative rancidity under the catalytic reaction of enzymes. Chemical and structural properties of lipids in CGs are affected by different treatments. Thermal and non-thermal effects prevent lipid oxidation or promote lipid combination with starch/protein in CG. Thus, the functional properties and final quality of CG are directly changed. In this review, the chemical composition and application of CGs especially the endogenous lipids are summarized and the effects of various processes on CG lipids/matrices are discussed for CG future development.